1994
DOI: 10.1007/bf02052589
|View full text |Cite
|
Sign up to set email alerts
|

Squamous-cell carcinoma of the anus in HIV-positive patients

Abstract: It would seem reasonable to offer combined modality treatment to early stage, HIV-positive patients with good performance status and a history of minor opportunistic infections. The value of combined modality in AIDS patients and those who present with advanced stages of the disease is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 20 publications
4
35
0
Order By: Relevance
“…Their HIV-positive patients had a 29 percent two-year survival. Chadha et al 12 reported the results of treating nine patients with HIV, eight of whom were available for a median follow-up of eight months. Although only one patient was able to complete the prescribed XRT and two cycles of chemotherapy with 5-fluorouracil and mitomycin C, seven patients revealed a complete clinical response.…”
Section: Discussionmentioning
confidence: 98%
“…Their HIV-positive patients had a 29 percent two-year survival. Chadha et al 12 reported the results of treating nine patients with HIV, eight of whom were available for a median follow-up of eight months. Although only one patient was able to complete the prescribed XRT and two cycles of chemotherapy with 5-fluorouracil and mitomycin C, seven patients revealed a complete clinical response.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 But this regimen is poorly tolerated by HIV+ patients and some authors have recommended lowering the dose and/or intensity of chemotherapy or radiotherapy. 13,14 Most of the patients from such studies were treated before the era of HAART. The availability of these new agents has rapidly changed the natural history and therapeutic results obtained in AIDS patients.…”
mentioning
confidence: 99%
“…Given the long-term survival rates that are possible for HIVinfected patients under modern antiretroviral combination therapy [14], long-term side effects of organ-preservative therapy are of interest. In our experience and that of others T2 N1 M0 T1 N0 M0 T3 N2 M0 T2 N0 M0 T1 N0 M0 T2 N0 M0 HIV-positive since (years) [5,8,15], there is no increased late complication rate and the reported side effects (1 patient with grade 1 anal stenosis, 1 patient with grade 2 pelvic and defecation pain) do not compromise the ability to participate in everyday life.…”
Section: Discussionmentioning
confidence: 75%
“…Initial reports on combined modality therapy for HIV-infected patients with epidermoid cancer of the anal canal were more or less casuistic contributions on treatment tolerance, rarely differentiating between patients with good performance status and those with fully developed AIDS. More than half of the patients described by Bottomley et al [7] (n = 5 patients), Peddada et al [5] (n = 8), Chadha et al [8] (n = 9), and Holland and Swift [15] (n = 7) needed treatment interruptions due to excessive side effects, even though treatment schedules in many cases already had been modified from institutional standards. The results reported here are an extension of a prior report [13] with long-term follow-up now available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation